Short Communication: The effects of vermicompost and vermiwash from the medicinal plants, neem (Azadirachta indica) and lime (Citrus aurantifolia), on the growth parameters of lettuce in a hydroponic system - SIRPAUL JAIKISHUN; AARIFA HOOSEIN; ABDULLAH ADIL ANSARI (Smujo International, 2018)
Jaikishun S, Hoosein A, Ansari AA. 2018. The effects of vermicompost and vermiwash from the medicinal plants, neem (Azadirachta indica) and lime (Citrus aurantifolia), on the growth parameters of lettuce in a hydroponic system. Nusantara Bioscience 10: 91-95. The farming community is confronting critical issues on the usage of chemicals and rapidly decreasing arable lands from salinity, flooding and drought. This study was designed to compare the effectiveness of vermiwash produced from medicinal plants, as a potential substitute for chemicals, and standard hydroponic solution in supporting the growth of lettuce in a hydroponic system, a soilless medium. Vermicompost and vermiwash were produced from Azadirachta indica, and Citrus aurantifolia using Eisenia fetida and physiochemical analyses done indicated the presence of adequate amount of nutrients for plant growth. Therefore, using vermiwash and vermicompost as a standard hydroponic solution is an efficient and effective method of growing more food for the world’s growing population in soilless medium, thereby reducing the dependency on land. Plants grown in the vermiwash and vermicompost in the hydroponic system had higher productivity than the one produced by commercial hydroponic solution.